2020
DOI: 10.3390/molecules25215074
|View full text |Cite
|
Sign up to set email alerts
|

Carbonation and Chloride Ions’ Penetration of Alkali-Activated Materials: A Review

Abstract: Alkali-activated materials (AAMs) are widely recognized as potential alternatives to ordinary Portland cement (OPC) due to their lower carbon footprint. However, like OPC, AAMs can also generate some durable problems when exposed to aggressive environments and the mechanisms and possible improvements are still not fully clear in existing investigations. Furthermore, the corrosion mechanisms of AAMs are different from OPC due to the discrepant reaction products and pore structures. Thus, this study’s aim is to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 161 publications
(335 reference statements)
0
9
0
Order By: Relevance
“…In general, in AAMs and geopolymers, fluid penetration through the material occurs due to the presence of an open-pore system [ 12 ]; additionally, the transport mechanisms in these materials are similar to cementitious binders and have been well investigated [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In general, in AAMs and geopolymers, fluid penetration through the material occurs due to the presence of an open-pore system [ 12 ]; additionally, the transport mechanisms in these materials are similar to cementitious binders and have been well investigated [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that porosity, pore size distribution, and tortuosity strongly affect mechanical properties and chloride transport in hardened concretes [31,53,54]. Each material was also subjected to a porosity analysis using mercury porosimetry using Poromaster Micromeritics AutoPore IV.…”
Section: Methodsmentioning
confidence: 99%
“…1. After 7 days of exposure to accelerated carbonation, mix S1 exhibited the highest carbonation depth, which can be explained by the lower alkali content than in the mix S2 and the lowest Ms of all three mixes [3,11,12]. Increase in Ms is expected to provide the best performance in terms of carbonation resistance due to the formation of less porous matrix structure [12].…”
Section: Carbonation Depthmentioning
confidence: 97%
“…It is reported that higher alkali content (%Na2O) and higher silica modulus (Ms) of the mix (i.e., SiO2/Na2O) improve the carbonation resistance [3,11,12]. A higher alkali content may result in higher activation degree of the slag, while a higher Ms results in a denser matrix and lower permeability due to slower slag hydration, which in turn results in a more uniform distribution of hydration products [3,6,10].…”
Section: Introductionmentioning
confidence: 99%